Size effect of porous filler in mixed matrix membranes for faster hydrogen permeation from methane-containing mixtures - Yuebing Shen; Fanfan Jiang; Qian Liu; Zhiquan Chen; Kai Ge; Junfeng Bai; Jingui Duan (Advanced Membranes, 2025)
One potential solution for the transport of hydrogen (H2) is the injection of hydrogen into natural gas pipelines. Therefore, it is imperative to develop an efficient purification technology. Membrane separation has great potential to meet this challenge due to its effective energy consumption and cost. Here, a series of mixed matrix membranes (MMMs) containing ZIF-71 fillers of different sizes are reported for faster H2 permeation. The uniform distribution of nanosized ZIF-71 (0.1 ​μm) in 6FDA-DAM provides an attractive diffusion channel, allowing the membrane to show rapid H2 permeation of 1050 Barrer and good H2/CH4 separation factor of 43. This performance is markedly superior to that of the larger-sized ZIF-71 (1.0 ​μm and 3.5 ​μm) in 6FDA-DAM and the same-sized ZIF-71 (0.1 ​μm) in 6FDA-Durene and PEI, and also exceeds the upper bound. Moreover, the long-term stable H2/CH4 separation suggests a high potential for practical applications. The findings here demonstrate the importance of the filler size, which has a strong influence on the formation of mass transfer channels, and also provide straightforward method for the development of high-performance MMMs.